Accelerating innovation with prize rewards: History and typology of technology prizes and a new contest design for innovation in African agriculture - Masters, William A.; Delbecq, Benoit (International Food Policy Research Institute, 2008)
This paper describes how governments and philanthropic donors could drive innovation through a new kind of technology contest. We begin by reviewing the history of technology prizes, which operate alongside private intellectual property rights and public R&D to accelerate and guide productivity growth towards otherwise-neglected social goals. Proportional prize rewards" would modify the traditional winner-take-all approach, by dividing available funds among multiple winners in proportion to measured achievement. This approach would provide a royalty-like payment for incremental success. The paper provides concludes with a specific example for how such prizes could be implemented to reward and help scale up successful innovations in African agriculture, through payments to innovators in proportion to the value created by their technologies after adoption. "